Distribution of natural and anthropogenic radionuclides in northwest Mediterranean coastal sediments. (June 2017) - Lee, Sang-Han; Povinec, Pavel P.; Chisholm, John R.M.; Levy, Isabelle; Miquel, Juan-Carlos; Oh, Jung-Suk
Abstract: The distribution of radionuclides in NW Mediterranean coastal sediments, and the processes controlling their abundance were investigated in three cores taken near the island of Porquerolles and one offshore Monaco. The sediments collected near Porquerolles were strongly anoxic due to diagenetic processes involved in the decomposition of organic matter, whereas they transitioned from oxic to anoxic at a depth of 4 cm beneath the seawater interface at Monaco. Organic carbon (OC) was more abundant in sediments at Porquerolles (by about a factor of 3–5) than at Monaco and elsewhere in the coastal NW Mediterranean. Sediment cores collected NE of Porquerolles also possessed elevated uranium concentrations that correlated with high OC content and strong reducing conditions. The 239, 240 Pu and 241 Am activities in surficial sediments ranged from 1 to 5.7 Bq kg −1 and 0.3 to 1 Bq kg −1, respectively, while the 137 Cs activity ranged from 0.3 to 6.2 Bq kg −1 . The mean activity ratios of 241 Am/ 239, 240 Pu and 238 Pu/ 239, 240 Pu in Porquerolles and Monaco sediments were similar to the global fallout ratios. Sediment inventories of global fallout 239, 240 Pu (430–800 Bq m −2 ) and 241 Am (150–285 Bq m −2 ) were by about a factor of 5–10 higher at Porquerolles, whereas the inventory of 137 Cs (430–1000 Bq m −2 ) was substantially lower at the investigated stations than have been reported elsewhere at similar latitudes. Specific local conditions characterised by high OC sediment loads due to the growth and mortality of Posidonia oceanica have been responsible for deposition of large amounts of seagrass tissues at the NE corner of Porquerolles, which have had a profound effect on the distribution of radionuclides in the sediments. Highlights: Radionuclides in coastal sediments of NW Mediterranean were investigated. 241 Am/ 239, 240 Pu and 238 Pu/ 239, 240 Pu ratios consistent with global fallout ratios. 137 Cs mostly dissolved, but 239, 240 Pu and 241 Am are particle reactive elements. Inventories of 239, 240 Pu (430–800 Bq m −2 ) and 241 Am (150–285 Bq m −2 ) are high. Inventories of 137 Cs are significantly lower at all stations investigated.